2016
DOI: 10.1039/c5ra23686j
|View full text |Cite
|
Sign up to set email alerts
|

A targeted agent with intercalation structure for cancer near-infrared imaging and photothermal therapy

Abstract: A new targeted photothermal agent is synthesized by co-intercalation of indocyanine green (ICG) and folic acid (FA) into the layered double hydroxide (LDH), which can be potentially used in cancer NIR imaging and photothermal therapy (PTT) field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 53 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…According to the previous reports, ,, the formation of J-aggregates of ICG molecules in LDH-based or Ag-based nanohybrids usually caused a relatively small redshift of ICG characteristic peak at about 20 to 50 nm. However, it was well known that modifying the electronic structure of π-conjugated organic compounds ( e.g.…”
Section: Results and Discussionmentioning
confidence: 82%
“…According to the previous reports, ,, the formation of J-aggregates of ICG molecules in LDH-based or Ag-based nanohybrids usually caused a relatively small redshift of ICG characteristic peak at about 20 to 50 nm. However, it was well known that modifying the electronic structure of π-conjugated organic compounds ( e.g.…”
Section: Results and Discussionmentioning
confidence: 82%
“…Finally, FA molecules were conjugated onto MT@L-PTX, and the final nanosystem MT@L-PTX@FA was obtained (Figure S8 revealed that the hydrodynamic size of MT@L-PTX@FA obtained from DLS was about 250 nm). As shown in Figure S9, the FT-IR spectra of MT@L-PTX@FA exhibited additional absorption bands at 1639 and 1401 cm –1 in comparison with that of MT@L-PTX, which were assigned to the symmetrical ν s (CO) and asymmetric ν as (CO) vibrations of FA, respectively, indicating the successful conjugation of FA.…”
Section: Resultsmentioning
confidence: 98%
“…Materials based on LDHs can be used as efficient HER and OER electrocatalysts due to their special layered structure, tunable band gaps, scale-up facility, great photocatalytic ability, and inexpensiveness. What is more, LDH microcrystals can be employed as monolayer nanosheets in fabricating electrocatalysts [30,31]. LDHs are made up of transition metal cations, especially Ti, Co, Fe, Ni, Mg, and Zn and are extensively employed in electrocatalytic reactions, particularly for HER and OER [32][33][34].…”
Section: Introductionmentioning
confidence: 99%